Nursing Information System pada Pelayanan Kesehatan - Reidha Fitri Nurbaeti; Rr Tutik Sri Hariyat (Journal of Telenursing (JOTING), 2023)
This study aims to determine how to implement the nursing information system in health services in hospitals. The research method used was a literature study on ten journals related to the Nursing Information System. The results showed that the effectiveness of NIS found that NIS can reduce the workload of nurses and increase client satisfaction. NIS makes hospital nurses more efficient in nursing care, increasing client satisfaction. In conclusion, electronic nursing documentation can make nurse performance more effective. However, nurses must have informatics and English skills to adapt quickly in this era. Keywords: Hospital Health, Nursing Electronic Documentation, Nursing Information System, Services